2009
DOI: 10.1021/ja902864h
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Photoinduced Charge Separation Distances in Donor−Acceptor Systems for Artificial Photosynthesis Using OOP-ESEEM

Abstract: The distance over which two photogenerated charges are separated in electron donor-acceptor systems for artificial photosynthesis depends on the structure of the system, while the lifetime of the charge separation and, ultimately, its ability to carry out useful redox chemistry depend on the electronic coupling between the oxidized donor and reduced acceptor. The radical ions produced by charge separation are frequently delocalized over the pi systems of the final oxidized donor and reduced acceptor, so that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 20 publications
1
63
0
Order By: Relevance
“…8 In contrast, EPR can probe exchange interactions of the order of 10 À3 cm À1 and lower. 2,3,9,10 In this study, we investigate electronic communication in linear copper porphyrin oligomers designed as molecular wires [11][12][13] by EPR spectroscopy via measurement of the exchange coupling between the copper centers. The copper oligomers chosen for this case study represent very large spin systems with Hamiltonian dimensions exceeding the capabilities of commonly used simulation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…8 In contrast, EPR can probe exchange interactions of the order of 10 À3 cm À1 and lower. 2,3,9,10 In this study, we investigate electronic communication in linear copper porphyrin oligomers designed as molecular wires [11][12][13] by EPR spectroscopy via measurement of the exchange coupling between the copper centers. The copper oligomers chosen for this case study represent very large spin systems with Hamiltonian dimensions exceeding the capabilities of commonly used simulation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…+ n k )/6. [23] We analyzed the echo decays and frequency spectra based on published formalisms [21] and extracted dipolar and exchange couplings directly from least-squares fittings of simulations to experimental time traces.T he distances between the individual radicals in the RPs of the two proteins were calculated using the point-dipole approximation, [19] D(r) = À2785 mT 3 r À3 . As is already evident from am ere inspection of the experimental data, the simulations confirmed that D is larger in EcPL than in DmCry (see Figure 1), thus indicating as horter separation between the radicals in the pair of spins in the former protein.…”
mentioning
confidence: 99%
“…[12d, 15] Herein, we present data from pulsed out-of-phase electron-spin-echo envelope modulation (OOP-ESEEM) EPR [16] spectroscopic studies that were performed to directly measure the strength of the exchange and dipolar interactions in the short-lived RP states of the Drosophila melanogaster cryptochrome (DmCry) and Escherichia coli DNAp hotolyase (EcPL), for which ET along the conserved Tr pt riad has been extensively studied by transient optical absorption spectroscopy. [11b,17] OOP-ESEEM has previously been applied to examine spin-correlated RPs in photosynthetic reaction centers, [18] donor-acceptor systems for artificial photosynthesis, [19] and, more recently,c omposite materials designed for organic photovoltaic devices. [20] In brief,t his EPR experiment comprises ac anonical two-microwave-pulse echo sequence [hn-t DAF -(x 1 ) x -t-(x 2 ) x -t-echo] applied after as hort laser pulse that initiates RP formation.…”
mentioning
confidence: 99%
“…OOP-ESEEM experiments used a sample of BDXANINI (FIG. 4), with the expected donor-acceptor distance of 26 Å, similar to Sample 1 in [58], but with naphthalimide (NI) rather than phthalimide (PI) derivative as the acceptor, and 2,5ditertbutylphenyl as the end group. BDXANINI was dissolved in 4-cyano-4 -pentylbiphenyl (5CB) liquid crystal at a concentration of 0.2 mM and degassed in a 4 mm OD quartz tube using the freeze-pump-thaw method prior to flame sealing under vacuum.…”
Section: Methodsmentioning
confidence: 75%
“…The method has the benefit of a smaller number of experimental Figure 4: The sample used in OOP-ESEEM experiments on a photo-generated radical pair. The group that proposed this system [58] used BDX tag for the biphenyl dioxolane derivative on the left, ANI tag for the 4-aminonaphthalene-1,8-imide (middle), and NI tag for the naphthalene-1,8-imide-4,5-imide (right), hence the overall BDXANINI tag for the construct. evaluations per iteration compared to other gradient-free techniques, such as genetic algorithms [29,47] or simulated annealing [48].…”
Section: Optimisation Methodsmentioning
confidence: 99%